Age estimation of archaeological dogs using pulp cavity closure ratios. (November 2020) - Nomokonova, Tatiana; Losey, Robert J.; McLachlin, Kira; Bachura, Olga P.; Gusev, Andrei V.; Kosintsev, Pavel A.; Fedorova, Natalia V.; Sablin, Mikhail V.
Abstract: This study describes a non-destructive method that can be used to estimate the age of archaeological dog remains involving tooth pulp cavity closure ratios. This technique was first developed in wildlife management and zoology for wild carnivores. For the first time, we develop this technique for dogs by utilizing a modern sample of 751 teeth roots from 106 animals with known life histories. The method involves measuring widths of teeth roots and their pulp cavities by means of X-ray images, and then calculating the ratios of pulp cavity infilling for each tooth. The method is developed for upper and lower canines and the distal and mesial roots of the mandibular M1. Our assessments demonstrate that upper and lower canines are most strongly correlated with age, followed by the mesial and distal roots of the mandibular M1. The method is useful for assigning specimens to relative age categories, and proved most reliable with younger individuals. We illustrate the applicability of the method by analyzing 369 teeth roots from 77 archaeological dogs from the Iron Age Ust'-Polui site in Arctic Siberia. Previously, ageing of the dog remains at this site involved only assessments of dental eruption patterns and long bone epiphysis fusion. The overall age estimation results from Ust'-Polui produced a mortuary profile dominated by juveniles and prime age adults, suggesting a regional preference for dogs of these age groups in sacrifices. Highlights: Pulp cavity closure ratios are utilized for age estimation in dogs. Procedure is non-destructive and provides relative age estimates. Ageing method is applied to upper and lower canines and mandibular M1. Pulp cavity closure ratios of canines have strongest correlation with age. Method is applied to dog teeth from the Ust'-Polui site in Arctic Siberia.